Tools and algorithms for the construction and analysis of systems 17th international conference, TACAS 2011, held as part of the joint european conferences on theory and practice of software, ETAPS 2011, Saarbrücken, Germany, March 26-April 3, 2011. Proceedings - Abdulla, Parosh Aziz; Leino, K. Rustan M (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 17th International Conference on Tools and Algorithms for the Construction and Analysis of Systems, TACAS 2011, held in Saarbrücken, Germany, March 26?April 3, 2011, as part of ETAPS 2011, the European Joint Conferences on Theory and Practice of Software. The 32 revised full papers presented were carefully reviewed and selected from 112 submissions. The papers are organized in topical sections on memory models and consistency, invariants and termination, timed and probabilistic systems, interpolations and SAT-solvers, learning, model checking, games and automata, verification, and probabilistic systems